Effects of mindfulness intervention on competition state anxiety in sprinters—a randomized controlled trial - Yu, Ming Ge; Dou, Guang Bo; Gong, Chen (Frontiers in Psychology, 2024)
Objectives: The psychological problems of sprinters have become a common concern in sports training theory and practice with the rapid growth of the international competitiveness of China's sprint program. Hence, the work was to examine the impact of a 7-week positive thinking training program on state anxiety in Chinese sprinters. Methods: Twenty-four sprinters (M age = 22.46 ± 1.351) were selected in a 2 × 3 mixed design, with the group (mindfulness/control) as the between-subjects variable and test time (pre-test/mid-test/post-test) as the within-subjects variable. The dependent variables corresponded to the mindfulness score and competition state anxiety score. One 60-min session was conducted once a week for 7 weeks, and the control group did not undergo any psychological training. The mindfulness group received mindfulness training, and the control group received regular psychological guidance. The subjects filled in the Five Facet Mindfulness Questionnaire (FFMQ) and the Competition State Anxiety Scale at baseline, followed by additional assessments three weeks and seven weeks later. Results: (1) In terms of competition state anxiety, there were no significant differences in the pretest between the mindfulness group and the control group. There were significant differences in sprinters' competition state anxiety after mindfulness intervention in terms of time, group, and the interaction between time and groups (p = .03, .004, and. 009). (2) In terms of the mindfulness level, the difference between the mindfulness group and the control group was not significant in the pre-test. The sprinters' mindfulness level was significant in the interaction between groups and that between groups and time after mindfulness intervention (p = .027 and .028). Conclusions: Mindfulness training alleviated sprinters' competition anxiety by reducing sprinters' somatic state anxiety (SSA) and cognitive state anxiety (CSA) as well as improving state self-efficacy. Results provide guidance and references for Chinese sprinters' psychological problems.